Independent scientific research entities in New Zealand: Cawthron Institute as a case study - Hodder, Peter (New Zealand Science Review, 2018)
New Zealand Science Review Vol 75 (1) 20183The Cawthron Institute in Nelson is used as a case study in the history of the management of science in New Zealand, set against the background of the development of DSIR in the 1920s and the science reforms of the 1980s–1990s. The early scientific and managerial successes of the Cawthron scientific research institute enabled it to build relationships with DSIR, while still remaining committed to the application of the research undertaken to its region. The latter commitment has endured, and so the Institute is able to occupy the middle ground between the ‘industrial science’ of the Crown research institutes and the ‘academic’ science of universities, as do some individual scien-tists as contractors.